Vitamin A Orange Cassava: GKA 2011/274 - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Collaboration between HarvestPlus, CGIAR breeding centers, and NARS resulted in the release of 29 new varieties of vitamin A maize (hybrid and open pollinated varieties), cassava and orange sweet potato; zinc wheat; iron pearl millet and beans; and zinc and iron lentils